Processo integrado de gestão de pessoas: um modelo estratégico para aplicação em pequenas e médias organizações de Tecnologia da Informação - Rezende, Ricardo (2019)
REZENDE, Ricardo. Integrated People Management Process: a strategic model for application in small and medium Information Technology organizations . 2019. 74p. Dissertation (Masters) – Faculdade de Gestão e Negócios, Universidade Federal de Uberlândia, Uberlândia, 2019. The practice of People Management has been challenged by organizational, economic, sociological and technological changes that create countless opportunities for this management and for organizations as a whole, as it requires more effective and faster organizational adaptations. However, there is a lack of a process that interconnects the People Management subsystems with each other, and align them with the strategy of the organization, according to the objective of this paper, to present an integrated proposal of People Management processes aligned business strategy in the context of small and medium Information Technology organizations, as well as describe the application in one of these organizations. It is an applied research, exploratory and descriptive, with qualitative treatment of data. The Integrated People Management System developed by the author and described in the paper is the answer to the research question. By describing People Management with its interconnected processes and its integration with the organizational strategy, the conditions were created to assess its effectiveness. implementation in an Information Technology organization and the result of this application has been adherent to the reality of the organization and has contributed to the achievement of the organizational strategic objectives. This technological product is registered with the National Library Foundation in the city of Rio de Janeiro.